Dendroclimatic studies : tree growth and climate change in northern forests - D'Arrigo, Rosanne, 1954- (Special publication (American Geophysical Union) ;, 2014)
A top priority in climate research is obtaining broad-extent and long-term data to support analyses of historical patterns and trends, and for model development and evaluation. Along with directly measured climate data from the present and recent past, it is important to obtain estimates of long past climate variations spanning multiple centuries and millennia. Dendroclimatic Studies at the North American Tree Line presents an overview of the current state of dendroclimatology, its contributions over the past few decades, and its future potential. The material included is not useful n.